2020
DOI: 10.3389/fcell.2020.568894
|View full text |Cite
|
Sign up to set email alerts
|

Tectorigenin Alleviates Inflammation, Apoptosis, and Ossification in Rat Tendon-Derived Stem Cells via Modulating NF-Kappa B and MAPK Pathways

Abstract: Tendinopathy is a common musculoskeletal disorder that mainly affects athletes and people of older age. Tumor necrosis factor-α (TNF-α) plays an important role in initiating tendinopathy. Tectorigenin, an extract component of Belam-canda Chinesis, possesses anti-inflammatory and anti-apoptosis activity. The present study was established to investigate the role of tectorigenin against the pathogenetic effects of TNF-α on tendonderived stem cells (TDSCs) in vivo and in vitro. The findings indicated that TNF-α is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…Consistently, autophagy inhibitors could counteract the inhibitory effect of TEC on lipid droplet formation and enhance the expression of pyroptosis protein and release of LDH. Combined with TEC improving liver failure by regulating autophagy pathway, and TEC regulated TLR4, NF-κB and MAPK pathway to inhibit the occurrence of inflammatory response, which all proved our view that TEC may improve NASH by regulating hepatocyte autophagy and pyroptosis [ 23 , 44 ].…”
Section: Discussionmentioning
confidence: 73%
“…Consistently, autophagy inhibitors could counteract the inhibitory effect of TEC on lipid droplet formation and enhance the expression of pyroptosis protein and release of LDH. Combined with TEC improving liver failure by regulating autophagy pathway, and TEC regulated TLR4, NF-κB and MAPK pathway to inhibit the occurrence of inflammatory response, which all proved our view that TEC may improve NASH by regulating hepatocyte autophagy and pyroptosis [ 23 , 44 ].…”
Section: Discussionmentioning
confidence: 73%
“…And there are also studies suggesting that the activation of NF-κB can induce the activation of the MAPK pathway [62]. Another study showed that TNF-α can induce TDSC in ammation and apoptosis, and promote the development of tendinopathy by up-regulating the activation of MAPK and NF-κB pathways [63]. Our analysis of the difference in immune cell in ltration of the whole gene of the samples showed that the in ltration of M1 macrophages, activated mast cells, activated NK cells, and regulatory T cells (Tregs) in tendinopathy samples increased, while the in ltration of plasma cells and memory B cells decreased.…”
Section: Discussionmentioning
confidence: 99%
“…during joint degeneration, especially that of the cartilage, the levels of some inflammatory cytokines, (including TNF-α and IL-1β) are increased, and subsequently cause a progressive, cell-mediated cascade of molecular and structural deterioration (36,37). TNF-α and IL-1β exert their detrimental functions via multiple important intracellular cascades, such as the NF-κB and MAPK pathways (38,39), In general, TNF-α and IL-1β transmit inflammatory signals via their receptors and activate the phosphorylation of the IKK complex (40), which then phosphorylates IκBα (41). Subsequently, IκBα is unbound and phosphorylates NF-κB, which translocates into the nucleus to initiate the transcription of inflammatory products, catabolic enzymes and apoptotic mediators (42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%